2020
DOI: 10.1007/s11031-020-09822-w
|View full text |Cite|
|
Sign up to set email alerts
|

Is it still worth it? Applying expectancy-value theory to investigate the intraindividual motivational process of forming intentions to drop out from university

Abstract: The intraindividual process of study dropout, from forming dropout intention to deregistration, is of motivational nature. Yet typical studies investigate interindividual differences, which do not inform about intraindividual processes. Our study focused on the intraindividual process of forming dropout intention, and applied expectancy-value theory to analyze its motivational underpinnings. To expand research, we considered associations of intraindividual deviations in expectancy, intrinsic value, attainment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 89 publications
4
45
0
1
Order By: Relevance
“…interest value) corresponds to the value that someone attaches to a task and contains the subfactor students' interest. The interest value refers to the enjoyment felt when performing a task and is synonymous with the intrinsic motivation within self-determination theory (SDT), which has also been shown to be predictive for students' retention and academic development (Deci et al, 1996;Duchatelet & Donche, 2019;Schnettler et al, 2020;Eccles & Wigfield, 2020). Since both theories and empirical studies emphasise the importance of ability beliefs and interest value, we have focused on these two components in this study.…”
Section: Ability Beliefs Interest Value and Task Effortmentioning
confidence: 99%
See 3 more Smart Citations
“…interest value) corresponds to the value that someone attaches to a task and contains the subfactor students' interest. The interest value refers to the enjoyment felt when performing a task and is synonymous with the intrinsic motivation within self-determination theory (SDT), which has also been shown to be predictive for students' retention and academic development (Deci et al, 1996;Duchatelet & Donche, 2019;Schnettler et al, 2020;Eccles & Wigfield, 2020). Since both theories and empirical studies emphasise the importance of ability beliefs and interest value, we have focused on these two components in this study.…”
Section: Ability Beliefs Interest Value and Task Effortmentioning
confidence: 99%
“…In contrast, students without a strong belief in their own study-related abilities might report a low degree of career decidedness (Restubog et al, 2010). Interest value might be similar (Mikkonen et al, 2013;Schnettler et al, 2020): Students' low level of interest in their studies might be related to low career decidedness and the intention to drop out. A study investigating Chinese pre-service teachers showed that intrinsic motivation was the best predictor of satisfaction with the chosen profession (An et al, 2020).…”
Section: Ability Beliefs Interest Value and Task Effortmentioning
confidence: 99%
See 2 more Smart Citations
“…La intención de abandonar los estudios se considera una señal de alerta temprana de la deserción escolar (Brandstätter et al, 2006). Por ello, comprender las variables que la afectan puede facilitar el diseño de servicios de apoyo para evitar el abandono escolar (Schnettler et al, 2020). La intención de abandono debe considerarse un indicador de un patrón de apatía hacia los estudios, el cual, si se manifiesta a través de inasistencia a clases, postergación de trabajos o no presentación de exámenes, puede conducir a la deserción escolar (Moneta, 2011).…”
Section: Miedo Al Covid-19 E Intención De Abandono Escolarunclassified